Analyzing the deviation between farmers' Land transfer intention and behavior in China's impoverished mountainous Area: A Logistic-ISM model approach. (May 2020) - Zhang, Yuanxia; Halder, Pradipta; Zhang, Xiaoning; Qu, Mei
Highlights: Effective land management is key to optimizing agricultural production. Majority of farmers deviate from their land transfer intention in China's mountains. Property rights adjustments strongly discourage willing farmers to transfer land. Abstract: China's land transfer is an inevitable requirement for implementing the rural revitalization strategy in the new era. The speed and extent of land transfer are related to the sustainable development of China's agriculture and the process of realizing rural agricultural modernization. In practice, due to the imperfect land transfer market and related systems, the property income of the transfer farmers is insufficient, which leads to inconsistency between the intention and behavior of the farmers. Based on a field survey of rural households in Gansu Province's impoverished mountainous area, we first employ cross-analysis to qualitatively assess the deviation between farmers' land transfer intention and behavior. Second, we use a logistic-interpretative-structural model to empirically analyze the factors influencing such a deviation and the internal logical relationships of these factors. We find that a substantial deviation exists between farmers' land transfer intention and behavior, with 57.64 % of respondents having the intention to transfer, but no actual transfer behavior. Moreover, among the 12 factors identified that significantly affect this deviation, agricultural production enthusiasm is superficially the main direct factor, while agricultural production scale, non-agricultural income, satisfaction in agricultural subsidy policy, and the impact of disasters are the secondary, indirect factors. Meanwhile, the deep-rooted factors are the head of household's age, the presence of village cadres in the household, non-farm working hours, the size of the household's labor force, and difficulty in obtaining land transfer information, land types, and property rights intervention. Therefore, we conclude that in the process of land transfer, the leading role of village cadres should be strengthened, a transfer information exchange platform should be established, land policy should be strictly implemented, land adjustment should be reduced, the rural land exit guarantee mechanism should be improved, and the doubts of farmers regarding land transfer should be eliminated. These steps would make sure that the deviation between farmers' land transfer intention and actual behavior is minimized.